Penetapan Kadar Mineral Mangan, Natrium Dan Besi Pada Sari Labu Siam (Sechium Edule Jacq Swartz) Tua Dan Muda Menggunakan Metode Spektrofotometri Serapan Atom - Irfan Ahmad Dasuki Nasution; Anny Sartika Daulay (Journal of Health and Medical Science, 2025)
Chayote (Sechium edule (Jacq.) is a plant that comes from the cucurbitaceae family. This plant is a vegetable that grows in the subtropics which is used as food and is also used in medicine. Chayote contains secondary metabolites, minerals and vitamins. Minerals contained in chayote include calcium, magnesium, sodium, phosphorus, zinc, iron and manganese. The purpose of this study was to determine the mineral content of manganese, sodium and iron from old and young chayote and to determine the differences in mineral content in old and young chayote. Samples were taken by positive sampling at the Simpang Limun market, Medan Amplas, North Sumatra. The sample consisted of old chayote and young chayote. The samples were treated by wet digestion. The assay was carried out using atomic absorption spectrophotometry with air-acetylene flame. Quantitative analysis of manganese, sodium and iron was carried out at wavelengths of 589.0 nm, 525 nm and 248.3 nm, respectively. The results showed that the levels of manganese, sodium and iron minerals in the old chayote were (0,1382±0,0036) mg/100g, (0,1382±0,0036) mg/100g, (0,2937±0,0029) mg/100g. The mineral content of manganese, sodium and iron in young chayote were (0,0758±0,0121) mg/100g, (9,8703±0,0335) mg/100g, (0,3438±0,0072) mg/100g.There is a difference between the mineral content found in old chayote and young chayote with manganese and iron content in young chayote which is higher than old chayote and sodium content in old chayote is lower than young chayote.